2005 Annual Conference Proceedings
DOI: 10.18260/1-2--14180
|View full text |Cite
|
Sign up to set email alerts
|

Using A Materials Concept Inventory To Assess An Introductory Materials Class: Potential And Problems

Abstract: In every engineering course there is a concern about how much the students are actually learning. The physics community has addressed this through the development of an assessment instrument called the Force Concept Inventory. More recently this has been expanded to the development of Engineering Concept Inventories. Universities affiliated with the N.S.F. sponsored Foundation Coalition have developed a number of these inventories. A Materials Concept Inventory has been developed by faculty from Arizona State … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the new format, we also implemented a conceptual pre-and post-quiz (the same quiz, up to some cosmetic changes, taken at the beginning and end of the course) based on the materials concept inventory by Krause et al [4]- [6]. Data from these quizzes is shown in Figure 4; student gains (the difference in the average score between pre-and post-quizzes were 26% in AU20, 28% in SP21, and 27% in AU21, and 26% in SP22) were between the gains found using the materials concept inventory with and without active learning [4], [7], but a direct comparison is not possible, as some of the questions used were cut or modified to match the different content covered. Instead, this data suggests the above course design is at least as effective as traditional instruction, and we also use this data semester-to-semester to refine our teaching of topics in which students continue to struggle.…”
Section: Resultsmentioning
confidence: 98%
“…In the new format, we also implemented a conceptual pre-and post-quiz (the same quiz, up to some cosmetic changes, taken at the beginning and end of the course) based on the materials concept inventory by Krause et al [4]- [6]. Data from these quizzes is shown in Figure 4; student gains (the difference in the average score between pre-and post-quizzes were 26% in AU20, 28% in SP21, and 27% in AU21, and 26% in SP22) were between the gains found using the materials concept inventory with and without active learning [4], [7], but a direct comparison is not possible, as some of the questions used were cut or modified to match the different content covered. Instead, this data suggests the above course design is at least as effective as traditional instruction, and we also use this data semester-to-semester to refine our teaching of topics in which students continue to struggle.…”
Section: Resultsmentioning
confidence: 98%
“…The low exit scores from these introduction to materials courses are similar to those reported in the literature. 17 Note, in the Fall 2005 pre-test, it was not recorded which lecture section the student was in. However, comparing to the pre-test data for Spring 2006, there was essentially no variation in the lecture sections at the start.…”
Section: Control Gatementioning
confidence: 99%
“…It was found that students from various disciplines taking introductory MSE courses had typical pre-post conceptual gains for a MCI test 24,25 of that was typically limited to 7-15% when content is delivered by lecture-based courses. Responses on MCI questions indicated misconceptions were pervasive 25,26 , and often related to students' application of inappropriate analogies of Page 13.191.5…”
Section: How Well Do Engineering Students Learn Materials Science and Engineering?mentioning
confidence: 99%
“…One way is with pre-post tests with the MCI 7 which has been used at Arizona State and at some other institutions 24,29 with Douglas 30 demonstrating that the MCI is a valid instrument but needed improved reliability. Such assessment can be used to determine what pedagogies most effectively promote conceptual change.…”
Section: How Well Do Engineering Students Learn Materials Science and Engineering?mentioning
confidence: 99%